Student theatre in the sociocultural space of the european north - Mariya A. Kirillova (Высшее образование в России, 2022)
The article explores the role of student theatre in the process of familiarizing the studentsof MSHU to the culture and traditions of the countries of the European North in order toimprove their professional training and intercultural competence.